2020
DOI: 10.1111/imr.12893
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear innate sensors for nucleic acids in immunity and inflammation

Abstract: Innate sensors recognize pathogen‐associated molecular patterns (PAMPs) or damage‐associated molecular patterns (DAMPs) to initiate innate immune response by activating downstream signaling. These evolutionarily conserved innate sensors usually locate in the plasma membrane or cytoplasm. However, the nucleus‐localized innate sensors are recently found to detect pathogenic nucleic acids for initiating innate response, demonstrating a complicated crosstalk with cytoplasmic sensors and signaling molecules to form… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 113 publications
(148 reference statements)
0
24
0
Order By: Relevance
“…In our data, COVID-19 lung proteome showed unique enrichment of pathways which are known to be associated with virus infection, including mRNA decay and translation shutoff (Tanaka et al, 2012) (Figure 4C). Further, double-stranded RNA (dsRNA) and uncapped mRNA of the virus act as viral pathogen-associated molecular patterns (PAMPs) which trigger the innate immune response through recognition by pattern recognition receptors (PRRs) in the cytoplasm (Lin and Cao, 2020). By comparing with the SARS-CoV-2 protein interaction map (Gordon et al, 2020), 12 virus-host interacting proteins were dysregulated only in the lung, including stress granule-related factor G3BP1, mitochondrial protein TIM10, transcription regulator eIF4H, RING-type E3 ubiquitin ligase MIB1, pro-inflammatory cytokine receptor IL17RA, and member of Cullin RING E3 ligase 2 complex ZYG11B (Figure 4D).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In our data, COVID-19 lung proteome showed unique enrichment of pathways which are known to be associated with virus infection, including mRNA decay and translation shutoff (Tanaka et al, 2012) (Figure 4C). Further, double-stranded RNA (dsRNA) and uncapped mRNA of the virus act as viral pathogen-associated molecular patterns (PAMPs) which trigger the innate immune response through recognition by pattern recognition receptors (PRRs) in the cytoplasm (Lin and Cao, 2020). By comparing with the SARS-CoV-2 protein interaction map (Gordon et al, 2020), 12 virus-host interacting proteins were dysregulated only in the lung, including stress granule-related factor G3BP1, mitochondrial protein TIM10, transcription regulator eIF4H, RING-type E3 ubiquitin ligase MIB1, pro-inflammatory cytokine receptor IL17RA, and member of Cullin RING E3 ligase 2 complex ZYG11B (Figure 4D).…”
Section: Resultsmentioning
confidence: 99%
“…During virus replication, double-stranded RNA (dsRNA) and uncapped mRNA of virus, known as viral pathogen-associated molecular patterns (PAMPs), could trigger the innate immune response once recognized by the pattern recognition receptors (PRRs) in the cytoplasm 221 . According to the PRRs list 221 , we found CGAS was upregulated in the lung of COVID-19 patients ( Figure 5A, SI Figure 10a). The upregulation of CGAS further induces downstream response including Type I interferon secretion and the release of several other cytokines 222 .…”
Section: Multi-organs Proteomic Changes (Supple For Figures 6 and 7)mentioning
confidence: 99%
“…Our data showed that EIF4E was upregulated only in the lung of the COVID-19 patients (Figure 5A), which might be perturbed and hijacked by SARS-CoV-2. Further, double-stranded RNA (dsRNA) and uncapped mRNA of the virus act as viral pathogen-associated molecular patterns (PAMPs) that trigger the innate immune response through recognition by pattern recognition receptors (PRRs) in the cytoplasm (Lin and Cao, 2020). By comparing with the SARS-CoV-2 protein interaction map (Gordon et al, 2020), 12 virus-host interacting proteins were dysregulated only in the lung, including stress granule-related factor G3BP1, mitochondrial protein TIMM10, transcription regulator eIF4H, RING-type E3 ubiquitin ligase MIB1, pro-inflammatory cytokine receptor IL17RA, and member of Cullin RING E3 ligase 2 complex ZYG11B (Figure 4D).…”
Section: Sars-cov-2-associated Protein Regulation In the Lungmentioning
confidence: 99%
“…NLRC1 and NLRC2, also known as NOD1 and NOD2, were the first intracellular sensors of bacterial peptidoglycan to be discovered, [51][52][53] Nuclear sensors can contribute to innate immunity by shuttling to the cytoplasm upon activation to initiate signaling cascades there, or they can perform functions directly in the nucleus and exert epigenetic control or regulate mRNA modifications. 55 Their direct nuclear action is a unique characteristic among the PRRs and may allow nuclear sensors to act more quickly than cytosolic sensors.…”
Section: Other Intr Acellul Ar Prr Smentioning
confidence: 99%
“…55 Nuclear sensors must walk a fine line to avoid aberrant activation in response to self-nucleic acids while still being ready to eliminate foreign threats. Lin and Cao cover the mechanisms employed by these sensors to ensure this important differentiation is maintainedand describe how these sensors drive innate immune signaling 55.…”
mentioning
confidence: 99%